2019
DOI: 10.1038/s41598-019-54816-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of shift work in healthcare workers

Abstract: The immune system potentially plays an important mechanistic role in the relation between shift work and adverse health effects. To better understand the immunological effects of shift work, we compared numbers and functionality of immune cells between night-shift and non-shift workers. Blood samples were collected from 254 night-shift and 57 non-shift workers employed in hospitals. Absolute numbers of monocytes, granulocytes, lymphocytes, and T cell subsets were assessed. As read out of immune function, monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 47 publications
6
44
0
Order By: Relevance
“…Unfortunately, in the present study most IL-6 data were under the LOD and we could not make any clear conclusions as to whether shift workers suffered from a systemic inflammation with regard to IL-6 or whether there was an alteration seen after a night shift. With respect to the previous literature on how shift work and sleep relate to cytokines, our findings are partially in contrast with several previous studies (5,7,8,12,21) but in agreement with others (6,10,11). In a systematic review and meta-analysis on the link between sleep disturbance, sleep duration and inflammation, Irwin et al (3) found 72 studies assessing IL-6, TNF-alpha, and C-reactive protein (CRP).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unfortunately, in the present study most IL-6 data were under the LOD and we could not make any clear conclusions as to whether shift workers suffered from a systemic inflammation with regard to IL-6 or whether there was an alteration seen after a night shift. With respect to the previous literature on how shift work and sleep relate to cytokines, our findings are partially in contrast with several previous studies (5,7,8,12,21) but in agreement with others (6,10,11). In a systematic review and meta-analysis on the link between sleep disturbance, sleep duration and inflammation, Irwin et al (3) found 72 studies assessing IL-6, TNF-alpha, and C-reactive protein (CRP).…”
Section: Discussionsupporting
confidence: 86%
“…Also, in a recent study comparing 254 night shift workers with 57 non-shift workers, no association in relation to work status was detected on a range of cytokines. However, night work was associated with increased number of monocytes and lymphocytes (11). In a clinical review, Faraut et al (12) addressed the issue of shift work and immunity, and suggested several lines of further studies (e.g., use of non-invasive biological markers, conduct more longitudinal studies) to delineate the pathways by which circadian misalignment and short sleep may influence immunological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, a bimodal rhythmic cytokine secretion was found to phase-shift 4.5–6 hours earlier in peripheral blood mononuclear cells from people who had undergone simulated night shift work conditions than in those collected from people examined following simulated day shift work conditions [22] . Another study found that the average number of monocytes was 1.15 times higher in night-shift workers, and that night-shift workers who had worked night-shifts in the past three days had higher mean numbers of lymphocytes, T cells, and CD8+ T cells [23] . These alterations in immune response and cell subpopulations might also contribute to the increased risk for autoimmune diseases, cardiovascular and metabolic disorders, and cancer reported in night shift workers.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 97%
“…Cytokines and chemokines are important mediators of this immune response 28 30 . Infected ECD mice had higher secretions of the proinflammatory cytokines TNF-α and IL-1β in the first week of infection tapering off by the second week 15 , 31 . Excessive secretion of proinflammatory cytokines is associated with adverse pathological outcomes in the genital tract 32 35 .…”
Section: Discussionmentioning
confidence: 99%